Rare bird documentation form for Northern Goshawk at North Liberty, 1982 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1982)
Rare bird documentation form for a Northern Goshawk at North Liberty in Johnson County, IA on December 18, 1982. Epson - sheet feed